Effects of high dose retinoic acid on adult rat liver: electron microscopic and immunohistochemical study - Çolakoglu, N; Kükner, A (Pergamon-Elsevier Science Ltd, 2003)
The aim of the present study was to determine the effects of all-trans retinoic acid, a vitamin A metabolite, on liver structure. Twelve adult male rats were used and they were divided into three groups. The first group of rats was fed by gavage 20 mg/kg/day all-trans retinoic acid, whereas second group of rats received 40 mg/kg/day all-trans retinoic acid by gavage for 15 days. The rats in the 3(rd) group were used as control. At the end of the study liver tissue samples were taken under ether anesthesia and fixed in Bonin's and 2.5% glutaraldehyde solution for immunohistochemical and electron microscopic investigations. On light and electron microscopic investigations, we observed sinusoidal dilatation, periportal cellular infiltration, increase of lipid droplets in the Ito cells that correlated to the increase in the amount of all-trans retinoic acid. By immunohistochemical staining, diminished TGF-beta2 immune reaction in the hepatocytes of experimental groups and increased immune reaction in the sinusoidal space. However expression of TGF-beta2 was significantly increased in hepatocytes of which the infiltrating cells were abundant. As a result we observed that high dose of all-trans retinoic acid disturbed the normal liver structure. Thus, we concluded that structural changes occurred after RA administration was related to the increased dose of the agent and to the interrelation between RA and TGF-beta2 level. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: vitamin A; retinoic acid; liver; microscopy; TGF-beta 2